2016
DOI: 10.3892/ijo.2016.3817
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ST6GALNAC1 is associated with esophageal squamous cell carcinoma development

Abstract: Tylosis is an inherited disorder characterized by abnormal palmoplantar skin thickening and a highly elevated risk of esophageal squamous cell carcinoma (ESCC). Analyses of tylosis in families have localized the responsible gene locus to a region of chromosome 17q25.1. Frequent loss of heterozygosity (LOH) in 17q25.1 was also observed in the sporadic form of ESCC. A putative tumor suppressor gene for ESCC may exist at this locus. We investigated the expression patterns of genes on 17q25.1 in tumor and correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…ST6GALNAC1 encodes a sialyltransferase that acts as a catalyst for the synthesis of cancer-related sialyl-Tn (sTn) antigen critical for cell mobility [7]. It has been reported that ST6GALNAC1 was overexpressed in gastric, breast and prostate cancer cell lines, inducing sTn expression [811]. Previous findings have shown that ST6GALNAC1 played a part in elevating CSC phenotypes of colorectal cancer by activating the Akt signaling pathway [4].…”
Section: Introductionmentioning
confidence: 99%
“…ST6GALNAC1 encodes a sialyltransferase that acts as a catalyst for the synthesis of cancer-related sialyl-Tn (sTn) antigen critical for cell mobility [7]. It has been reported that ST6GALNAC1 was overexpressed in gastric, breast and prostate cancer cell lines, inducing sTn expression [811]. Previous findings have shown that ST6GALNAC1 played a part in elevating CSC phenotypes of colorectal cancer by activating the Akt signaling pathway [4].…”
Section: Introductionmentioning
confidence: 99%
“…(Manual review of the publication revealed paracancerous normal tissues as the reference.) Similarly, ST6GALNAC1 was identified to be downregulated in ESCC (Iwaya et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ST6GALNAC1 expression in the IA sac was significantly positively correlated with IA size. ST6GALNAC1 encodes a sialyltransferase involved in protein glycosylation and is activated by CCL17 through the NF-kB pathway signaling [58][59][60]. TIFAB, which encodes a regulator of TRAF proteins that transduce extracellular inflammatory signals that mediate the NF-kB pathway, was also positively correlated with aneurysm size (and with IA wall enhancement, albeit not significantly) [61,62].…”
Section: Discussionmentioning
confidence: 99%